3D–2D–0D Interface Profiling for Record Efficiency All‐Inorganic CsPbBrI2 Perovskite Solar Cells with Superior Stability. Issue 15 (24th January 2018) - Zhang, Jingru; Bai, Dongliang; Jin, Zhiwen; Bian, Hui; Wang, Kang; Sun, Jie; Wang, Qian; Liu, Shengzhong (Frank)
Abstract: All‐inorganic CsPbBrI2 perovskite has great advantages in terms of ambient phase stability and suitable band gap (1.91 eV) for photovoltaic applications. However, the typically used structure causes reduced device performance, primarily due to the large recombination at the interface between the perovskite, and the hole‐extraction layer (HEL). In this paper, an efficient CsPbBrI2 perovskite solar cell (PSC) with a dimensionally graded heterojunction is reported, in which the CsPbBrI2 material is distributed within bulk–nanosheet–quantum dots or 3D–2D–0D dimension‐profiled interface structure so that the energy alignment is optimized in between the valence and conduction bands of both CsPbBrI2 and the HEL layers. Specifically, the valence‐/conduction‐band edge is leveraged to bend with synergistic advantages: the graded combination enhances the hole extraction and conduction efficiency with effectively decreased recombination loss during the hole‐transfer process, leading to an enhanced built‐in electric field, hence a high V OC of as much as 1.19 V. The profiled structure induces continuously upshifted energy levels, resulting in a higher J SC of as much as 12.93 mA cm −2 and fill factor as high as 80.5%, and therefore record power conversion efficiency (PCE) of 12.39%. As far as it is known, this is the highest PCE for CsPbBrI2 perovskite‐based PSC. Abstract : Here, a 3D–2D–0D multi‐graded interface based on CsPbBrI2 bulk, nanosheets, and quantum dots is first designed for CsPbBrI2 perovskite solar cells. Such a multigraded surface favorably reduces the recombination at the CsPbBrI2 /poly[bis(4‐phenyl) (2, 4, 6‐trimethylphenyl)amine] interface, resulting in a record stabilized power conversion efficiency of 12.39%, a nearly 20% increase compared with 10.38% for ungraded devices.